REDUCTION DESIGN AND OPTIMIZATION ANALYSIS FOR VEHICLE BODY BASED ON TAILOR ROLLED BLANK TECHNOLOGY - CHENG JiangHong; WANG LiJuan; CHEN ZongYu; XU MingTao; FANG ZheLin (Jixie qiangdu)
Tailor Rolled Blank（ TRB） is an emerging steel rolling process to effectively produce lightweight vehicle components. It allows continuous metal thickness changes. Combining with the design method of body collision force transmission path and load flow reasonable distribution,optimization design and analysis of a SUV on critical parts structure was carried out based on the TRB technology,which have great effects on the vehicle body safety in side collision. Studies have shown that using the new TRB steel had caused the deformation of vehicle and the intrusion speed peak value of chest and pelvis reduced. The vehicle lightweight was cut down 5. 5kg,the number of automotive parts was reduced 5,while the crash safety was ensured.Accordingly,decreasing weld process,manufacturing procedure,and achieve the dual goals of crashworthiness and reduction.